2016
DOI: 10.1002/jbt.21839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pendimethalin binding to human serum albumin: Insights from spectroscopic and molecular modeling approach

Abstract: Interaction of pendimethalin (PM) herbicide with the major transporter in human circulation, human serum albumin (HSA), was studied using fluorescence, circular dichroism (CD), and molecular modeling methods. The attenuation of the fluorescence intensity of HSA in the presence of PM revealed formation of the PM-HSA complex. Analysis of the fluorescence quenching data showed moderately strong binding affinity between PM and HSA. Both hydrophobic interactions and hydrogen bonding were suggested to stabilize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…The value of the Stern–Volmer constant, K sv was determined from the slope of the Stern–Volmer plot. As can be seen from Table , the PM–GSA system had a value of K sv as 2.99 ± 0.03 × 10 5 M −1 , which was found to be similar to the K sv value (1.50 ± 0.01 × 10 5 M −1 ), reported for PM–human serum albumin system . The value of the bimolecular quenching rate constant, k q , as calculated from the K sv value, dropped into the range of 10 13 M −1 s −1 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The value of the Stern–Volmer constant, K sv was determined from the slope of the Stern–Volmer plot. As can be seen from Table , the PM–GSA system had a value of K sv as 2.99 ± 0.03 × 10 5 M −1 , which was found to be similar to the K sv value (1.50 ± 0.01 × 10 5 M −1 ), reported for PM–human serum albumin system . The value of the bimolecular quenching rate constant, k q , as calculated from the K sv value, dropped into the range of 10 13 M −1 s −1 .…”
Section: Resultssupporting
confidence: 78%
“…Value of n (Table ) also suggested the presence of a single PM binding site in GSA. In a recent study, a similar binding affinity ( K a = 2.09 ± 0.06 × 10 5 m −1 ) was reported between PM and human serum albumin . Such a binding affinity suggested an efficient transportation of PM in goat blood circulation.…”
Section: Resultssupporting
confidence: 65%
“…Albumin is not just passive, but an active participant in pharmacokinetic and toxicokinetic processes too. The esterase or pseudoesterase activity of albumin against α-naphthyl acetate and p -nitrophenyl acetate (NPA), FA esters, aspirin, ketoprofen glucuronide, cyclophosphamide, nicotinic acid esters, octanoyl-ghrelin, nitroacetanilide, p -nitrofluoroacetanilide and some OPs have been demonstrated in numerous experiments [ 56 , 66 , 67 , 68 ]. A typical example of the pseudoesterase activity of albumin is acetylation.…”
Section: Enzymatic Activity Of Albuminmentioning
confidence: 99%
“…As shown in Figure S5, peak a and peak b corresponded to the Rayleigh scattering peak (λ em = λ ex ) and the second-order scattering peak (λ em = 2λ ex ), respectively. 54,55 Moreover, peak 1 (the strong fluorescence peak) primarily revealed the spectral behavior of Trp and Tyr residues. 56 From Table S3, it could be found that an obvious reduction in the fluorescence intensity of peak 1 (for α-amylase, decreased by 28.65%; for α-glucosidase, decreased by 32.43%) was observed, and a red shift in the peak position was recorded (for the α- amylase−silibinin system, 3 nm; for the α-glucosidase− silibinin system, 4 nm) when silibinin was added into the enzyme solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%